2022
DOI: 10.3390/cancers14204973
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Lymph Node Gene Expression Signature Predicts Recurrence-Free Survival in Cutaneous Melanoma

Abstract: We sought to develop a sentinel lymph node gene expression signature score predictive of disease recurrence in patients with cutaneous melanoma. Gene expression profiling was performed on SLN biopsies using U133A 2.0 Affymetrix gene chips. The top 25 genes associated with recurrence-free survival (RFS) were selected and a penalized regression function was used to select 12 genes with a non-zero coefficient. A proportional hazards regression model was used to evaluate the association between clinical covariates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…C1QTNF3, known as an anti-inflammatory cytokine 46,68,69 , plays a role in stimulating macrophage chemotaxis during adipose tissue remodelling 70 . Intriguingly, it is one of the 12 prognostic genes linked to recurrence-free survival in human cutaneous melanoma 71 and is a significant gene associated with pigmentary traits 72 . Our analysis has revealed that late-emigrating, C1QTNF3 + bridge cells co-express both glial and melanocyte genes, excluding neuronal genes.…”
Section: Discussionmentioning
confidence: 99%
“…C1QTNF3, known as an anti-inflammatory cytokine 46,68,69 , plays a role in stimulating macrophage chemotaxis during adipose tissue remodelling 70 . Intriguingly, it is one of the 12 prognostic genes linked to recurrence-free survival in human cutaneous melanoma 71 and is a significant gene associated with pigmentary traits 72 . Our analysis has revealed that late-emigrating, C1QTNF3 + bridge cells co-express both glial and melanocyte genes, excluding neuronal genes.…”
Section: Discussionmentioning
confidence: 99%
“…Baseline levels of CD79a + B cells before BCG treatment predict poor treatment outcomes in male and female NMIBC patients [53], suggesting that the expansion of exhausted immune cell populations, including atypical B cells, may contribute to early disease recurrence [53]. Paradoxically, while the presence of tertiary lymphoid structures (TLS) is typically associated with improved cancer outcomes [54,55], a recent study indicated that pre-BCG TLS presence is a negative prognostic factor in NMIBC [56]. Moreover, B cell depletion increased the production of IFNγ/IL-2 and IL-13 and the intratumoral levels of CD8A, CXCL10, CXCL9, and BATF3 in response to BCG treatment [56], which is consistent with CTL recruitment and a shift toward the desirable Th1/CTL-dominated immune landscape [56].…”
Section: Bcg and Tumor Immunitymentioning
confidence: 99%